IMPLEMENTATION OF THEME-BASED PLAY LEARNING FOR EARLY CHILDHOOD COGNITIVE DEVELOPMENT - Okta Rianis Rahmawati; Dhini Anugrah (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2026)
Learning in early childhood education must be designed according to the characteristics of child development, especially through play-based activities that are integrated into thematic learning. This study aims to analyze the implementation of play-based thematic learning and its contribution to early childhood cognitive development. This study uses a qualitative descriptive approach with classroom observation techniques, teacher interviews, and documentation analysis in an early childhood education institution. The results showed that thematic play activities stimulate children's logical thinking, simple problem solving, number recognition, pattern formation, and understanding of cause and effect in a meaningful way. Children participate actively, show curiosity, and are able to relate the experience of play to the concept of learning. Therefore, play-based thematic learning is an effective learning strategy to foster early childhood cognitive development in a natural, meaningful, and sustainable way